Analisa Teknikal Pergerakan Harga Saham untuk Menentukan Keputusan Investasi yang Terdaftar di BEI (Studi pada Sektor Tambang) - Anita Nur Choiriyah; Anik Malikah; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The act of placing assets in the form of assets or funds in something that is anticipated to produce income or increase in value in the future is known as investment. Investors can invest in stocks using a long-term strategy to get profits, but there are other ways that can be used to develop funds from stock investment, namely stock trading (trading). This study aims to find out when the momentum is right to buy or sell shares in the mining sub-sector. This type of research uses descriptive qualitative, with a total of thirteen samples, this study uses four indicators, namely candlesticks, Moving Average, Relative Strange Index, and Fibonacci Retracement. The data used in secondary data research where the data is obtained from IDX. The results of this study resulted in seven investment recommendations for mining sector stocks that can be purchased in the 2019-2022 period. The author recommends choosing one of the thirteen samples, namely the MDKA company, because the movement of these shares is more stable, and each year has a very large profit.Keywords: Stock investment, investment decision, technical analysis, candlestick, moving average, relative strange index, fibonacci retracement, and stock recommendations